Association between tumor necrosis factor-α gene polymorphism and interleukin-6 level with mortality of neonatal sepsis - Darnifayanti, Darnifayanti; Akmal, Muslim; Nur, Syahrun; Yusuf, Sulaiman (Narra J, 2024)
Sepsis is a systemic infection that significantly causes morbidity and mortality among neonates, which is associated with immature immune response. Variations in the tumor necrosis factor-alpha gene (TNF-α) -308G/A may be linked to neonatal sepsis mortality by modulating interleukins (ILs) involved in the immune response cascade, such as IL-6. The aim of this study was to investigate the association between TNF-α -308G/A gene variation and IL-6 level with mortality of neonatal sepsis. A cohort of 30 neonates diagnosed with clinical sepsis was recruited. Blood culture was performed for all patients and serum IL-6 levels were examined 24 hours after suspected sepsis. Genetic analysis of TNF-α single nucleotide polymorphisms (SNP) -308G/A was conducted using polymerase chain reaction and DNA sequencing. The association was assessed based on bivariate logistic regression. We found that 12 (40%) of 30 patients had blood culture-proven sepsis. Genotype of TNF-α -308G/A stratified of the patients was 56.7% for GA and 43.3% for GG. There were no AA variations found in this study. There was no significant association between the TNF-α -308 G/A genotype and mortality in neonatal sepsis (p=0.211). Similarly, the allelic model of TNF-α -308 gene had no association with mortality (p=0.325). Additionally, there was no association between serum IL-6 level and mortality in neonatal sepsis (p=0.253). In conclusion, SNP of TNF-α -308 gene and IL-6 level are not associated with mortality in neonatal sepsis.